PENGARUH PENDEKATAN PEMBELAJARAN TAKTIS TERHADAP KETERAMPILAN SEPAKBOLA SISWA KELAS XISMA LABSCHOOL UPI KOTA BANDUNG - Ricky Fernando (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Research will study on the effectiveness of approach learning tactical of the results of learn the skill of football. The result of this research expected can be used as as alternative solutions in establishing the quality of learning football. Methods used in research this is the method his experiments with design pree-test post-test design. Population in this study were students the son of class XI high school labschool UPI Bandung city 60 students. Technique the sample collection using a technique purposive sampling. Time research which was during two months, the number of treatment 18 meeting, with the frequency of the 1 on sunday 3 times. An instrument selected writer is the test skill and football tests the ability of play (GPAI). To high school student test skill football (a pre-test and the end skill football) there are four who writers use the test passing and stoping, a heading, dribbling and shooting and tests the ability of play (GPAI). Based on the results of the analysis so can be concluded: (1) is the significant approach learning tactical of the results of learn the skill of football.